Pengaruh Perencanaan Pajak terhadap Keputusan Transfer Pricing pada Perusahaan Multinasional - Elia Rossa; Arinda Dwi Cahyani; Azhar Huwaiza Fathoni; Dara Dinanti; Denya Saputri; Dwi Renaldy Putra; Daudy Erickson (Akuntansi, 2024)
This research aims to examine the influence of tax planning on transfer pricing decisions in multinational companies. This research uses a literature study method. The theory used in this research is agency theory. The research results show that tax planning can be a consideration in making transfer pricing decisions in multinational companies. This research was conducted so that future researchers can understand in detail the theories and research results related to their research topic.